Evaluating school efficiency using data envelopment analysis / Paul Lau Ngee Kiong, Leong Siow Hoo and Hwa Tee Yong - Lau, Ngee Kiong; Leong, Siow Hoo; Hwa, Tee Yong; Mahdi, Rasidah (Research Management Institute (RMI), 2005)
This project intended to examine the determinants contributing to school efficiency based on the 'High Standard Quality Education 'framework compiled by the Malaysian School Inspectorate and to evaluate the relative efficiencies of all the sixteen secondary schools in the Sri Aman/Betong Division, Sarawak for the year 2002. This study collected the secondary data through the working manual of 'High Standard Quality Education' (PKSBSTKP). A set of forms and questionnaire were also designed to gather data on additional variables and the perceptions from the teachers and students on their schools. Several findings emerged. The PKSBSTKP performances of all the participating schools were average. The 6 inputs and 6 outputs of the PKSBSTKP could be reduced to 3 input variables and 3 output variables using the principal component analysis in order to increase the discriminating power of Data Envelopment Analysis (DEA). The nondiscretionary input variables had a profound impact on school efficiency. There are obvious differences in evaluating performances of schools by DEA and the methodology of PKSBSTKP. Nine schools were found to be efficient and seven schools were inefficient using DEA. However, there was no significant difference in the efficiencies between schools in the urban and rural areas of the Sri Aman/Betong Division. A set of efficient schools was also identified for each inefficient school to benchmark for improvement.